Current Trends in the Popular Sector Traditional Medicine in Sri Lanka: Traditional Medicine in Sri Lanka - Abeyrathne, Rathnayake M. (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
It is well known fact that Sri Lanka was able to produce a unique tradition of knowledge in the field of traditional medicine over the last two thousand five hundred years of its history. The country is placed where its inhabitants were able to develop a traditional medicine-based medical pluralism, comprising Desheeya Chikithsa, Ayurveda, Unani, Siddha, Homeopathy and various other informal traditions to as remedies cure various illnesses. In this paper, I focus on discussing major developments and trends in the popular sector traditional medicine in Sri Lanka at present. They include new trends in the use of traditional medicines as reliefs for minor illnesses, personal health and beautifying items, supplementary food substances and positive health and wellness practices. At present, traditional medicine-related items have become common consumable items among Sri Lanka public as a deterrent to control non-communicable diseases and traditional herbal products are more popular as beatification therapies. In order to minimize the problems that this sector faces, the state can take numerous measures such as strengthening the law to crack down illegal practitioners, register all service providers under the local government’s health departments and conduct periodic health campaigns to educate people about the importance of this sector as a way to prevent the etiologies of illnesses and diseases to promote health behavior in the long-run to combat the spared of all types of diseases and to cut down staggering cost of health expenses that people have to face in-day-to-day life.